Study on Phenotypical Activity of Isoenzyme CYP3A4 in Children - B. I. Kantemirova; A. KH. Chernysheva; A. K. Starodubtsev; D. A. Sychev (Антибиотики и Химиотерапия)
The urine levels of cortisol and 6-β-hydroxycortisol in 30 healthy children were determined with high performance liquid chromatography. The activity of cytochrome P450 isoenzyme CYP3A4 was estimated by the ratio of 6-β-hydroxycortisol and cortisol. Differences in the CYP3A4 activity depended on the age sex. At the age of 4 to 9 years the value of the ratio was 9.21+0.67 which in fact was statistically higher than that in the children at the age of 0 to 3 years (p